Pengembangan Aplikasi Mobile Translator Menggunakan Mit App Inventor - Ode Rintik Segara; Sularno (GLOBAL SCIENTS PUBLISHER, 2024)
Mobile application development has become an important need in today's digital era. One particularly useful app is a language translator app, which facilitates cross-language communication effectively. This article discusses developing a translator application using MIT App Inventor. The drag-and-drop approach provided by MIT App Inventor allows developers, especially beginners, to create mobile applications without having in-depth programming knowledge. This application is designed to translate text from one language to another directly, utilizing a simple user interface to make it easier for users to interact with the application.